Hydrogen Storage in Iron/Carbon Nanopowder Composite Materials: Effect of Varying Spiked Iron Content on Hydrogen Adsorption. (20th March 2013) - Chu, Chun-Lin; Chang, Chia-Feng; Chen, Jiann-Ruey; Fuh, Yiin-Kuen
Abstract : This study investigates the effects of varying the spiked iron content of iron/carbon nanopowder (Fe/CNP) composite materials on hydrogen storage capacity. Among four such samples, a maximum hydrogen uptake of approximately 0.48 wt% was obtained with 14 wt% of spiked iron under 37 atm and 300 K. This higher hydrogen uptake capacity was believed to be closely related to the physisorption mechanism rather than chemisorption. In this case, the formation of maghemite catalyzed the attraction of hydrogen molecules and the CNP skeleton was the principal absorbent material for hydrogen storage. However, as the iron content exceeded 14 wt%, the formation of larger and poorly dispersed maghemite grains reduced the available surface areas of CNP for the storage of hydrogen molecules, leading to decreased uptake. Our study shows that hydrogen uptake capacities can be improved by appropriately adjusting the surface polarities of the CNP with well dispersed iron oxides crystals.